Contribution of immune cells in synergistic anti-tumor effect of ablation and immunotherapy - Ningning He; Jingting Jiang (Translational Oncology, 2024)
Thermal ablation results in the damage of tumor tissue, which leads to localized necrosis and incites a significant inflammatory response, accompanied by the infiltration of numerous immune cells. Nevertheless, depending solely on the singular approach of thermal ablation frequently is difficult in eliciting a robust anti-tumor response. Research suggests that integrating immune modulators into conventional ablation techniques has the potential to enhance the elicited immune response, finally initiating synergistic effect without significantly elevated risk profiles. This article comprehensively analyses the immunological effects resulting from post-ablation alone and its synergy with immunotherapies, and accentuates the heterogeneous alterations noted in immune cells across distinct malignancies. Collectively, the article delves into the theoretical framework and advancements in clinical trials concerning the combined thermal ablation and immunotherapy for treating malignant tumors.